Women and Hoax News Processing on WhatsApp - Hani Noor Ilahi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
The word hoax became popular with the development of technology that has potentially increased the circulation of hoax news. One of the ways hoax news circulates is through mobile instant messaging applications like WhatsApp, where users can interact directly, or between individuals who are members of a group. In Indonesia, by 2017, WhatsApp was the most used and the longestused mobile instant messaging application, having 35.87 million users. This study focuses on women using WhatsApp, as previous studies have shown that women dominate social media use in Indonesia. Using the elaboration likelihood model, this study aimed to investigate how women process hoax messages about child abduction on WhatsApp. The results of research through interviews and surveys indicate that women tend to process hoax messages about the abduction of children through peripheral lines. The lack of media literacy and the tendency to prioritize the emotional aspects of a story make some women vulnerable to spreading hoaxes through WhatsApp. In this study, the researchers recommend a digital empowerment movement to improve women’s media literacy through an online lecture model on WhatsApp. This program should be professionally managed by experts or academics from relevant fields of study.